Content validity of patient-reported outcome measures for patients with chronic pain: considering the patient's perspective. Issue 2 (15th May 2022) - Hickey, Michael; Barry, Daniel; Redito, John; Anand, Natasha; Bianchi, Nancy; Reneman, Michiel; Escorpizo, Reuben
Abstract : Supplemental Digital Content is Available in the Text. Abstract: Understanding chronic pain and disability requires a consideration of the lived experience of the patient. There is limited evaluation of the content validity of patient-reported outcome measures (PROMs) in chronic pain using a comprehensive biopsychosocial view of the patient's experience. To address this gap, this study aimed to evaluate the content validity of PROMs for patients with chronic pain. A literature review was performed to identify PROMs for patients with chronic pain. Concepts from PROMs were linked to the International Classification of Functioning, Disability, and Health (ICF); the ICF Core Set for Chronic Widespread Pain; and the International Classification of Diseases-11 Functioning Properties of Chronic Pain (FP). Concepts were compared with published "attributes'' of chronic pain. 62 PROMs (1336 items total) were identified and linked to 560 unique second-level ICF categories. The greatest number of items across PROMs were represented in the activities and participation category (44% of all total items), followed by body functions (41%), environmental factors (9%), personal factors (5%), and body structures (0.3%). There was a 41% to 78% match with the Core Set for Chronic Widespread Pain and the International Classification of Diseases-11 FP, respectively. 20% of items reflected the pain-experience attributes with the most items reflecting the concept of "control over pain." Content validity analysis suggests chronic widespread pain patient-reported outcome measures poorly address attributes of living with chronic pain that matter most to patients. Future development or refinement should consider a more comprehensive view of the patients' lived experience.